2015
DOI: 10.1016/j.jjcc.2014.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial performance index derived from pre-ejection period as a novel and useful predictor of cardiovascular events in atrial fibrillation

Abstract: In AF patients, the PEPa-derived MPI was a useful predictor of adverse cardiovascular events and could offer an additional prognostic benefit over conventional clinical and echocardiographic parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Previous studies have utilized the PEP-derived MPI to evaluate LV function in AF patients. 8 , 9 , 29 Recently, it was reported that the PEPa-derived MPI was a useful predictor of adverse cardiovascular events, and could offer an additional prognostic benefit over conventional clinical and echocardiographic parameters in patients with AF. 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have utilized the PEP-derived MPI to evaluate LV function in AF patients. 8 , 9 , 29 Recently, it was reported that the PEPa-derived MPI was a useful predictor of adverse cardiovascular events, and could offer an additional prognostic benefit over conventional clinical and echocardiographic parameters in patients with AF. 9 …”
Section: Discussionmentioning
confidence: 99%
“… 8 PEP interval was measured from the onset of QRS to the onset of the systolic mitral annular velocity pattern. Su et al 9 defined the “PEPa-derived MPI” in patients with AF; it is calculated as the ratio of PEPa along with IVRTa to ETa. In a recent study, it was reported that the PEPa-derived MPI was a useful predictor of adverse cardiovascular events, and could offer an additional prognostic benefit over conventional clinical and echocardiographic parameters in patients with AF.…”
Section: Introductionmentioning
confidence: 99%
“…In another study that observed 190 patients with AF, increased average E/e' was related to death and hospitalization for heart failure in univariate analysis (p<0.001) [55] . In another observational study that prospectively followed 196 consecutive patients with AF for about 17 months, an abnormal value for average E/e' was associated with sudden death, stroke and hospitalization for heart failure (p =0.001), after adjusting for chronic heart failure (p = 0.002) and the myocardial performance index (p = 0.004) [56] . Similar results have been reported in another observational study that followed 252 consecutive patients with AF for 21 months [57] .…”
Section: Relevance Of E/e' In Risk Stratification In Patients With Afmentioning
confidence: 98%
“…15 Eight studies compared echocardiographic indices of systolic function with clinical parameters or surrogate biomarkers. [16][17][18][19][20][21][22][23] In 1293 AF patients who had suffered a myocardial infarction, lower LVEF (estimated using an echocardiographic wall motion score) was associated with an increase in the risk of 30-day mortality (8% for patients with LVEF >50%, 10% for LVEF 36-50%, 24% for LVEF 26-35% and 40% for LVEF <25%). 19 However, lower LVEF did not appear to predict long-term mortality in AF patients.…”
Section: Echocardiographymentioning
confidence: 99%